Professor James E. Tomayko. - Tomayko, James E. (Software engineering notes.)
Carnegie Mellon professor and alumnus James Tomayko (HS'71,'80), a founder and former director of the Master in Software Engineering (MSE) program in the School of Computer Science (SCS), died on Monday, Jan. 9, 2006, after a long illness. He was 56.